Taphonomy of fish, invertebrates and plant remains in the first Tethyan-South Atlantic marine ingression along Cretaceous rift systems in NE-Brazil - Voltani, Cibele Gasparelo; Osés, Gabriel Ladeira; Freitas, Bernardo Tavares; Prado, Gustavo Marcondes Evangelista Martins; Rohn, Rosemarie [UNESP]; Pacheco, Mírian Liza Alves Forancelli; Anelli, Luiz Eduardo; de Almeida, Renato Paes; Simões, Marcello Guimarães [UNESP]; Caldeira do Prado, Ludmila Alves; Araripe, Rilda Verônica Cardoso de; Galante, Douglas; et al. (Elsevier, 2023)
The Aptian–Albian Amargosa Bed, Tucano Basin, which was recently considered as a Konservat-Lagerstätten, is a relatively thin, siliciclastic-dominated succession of yellowish and grayish papyraceous shales. We analyzed the taphonomy of fishes, gastric ejecta, freshwater shrimps and conchostracans, euryaline ostracods, and plants. Fish biostratinomic signatures indicate point to changes in water alkalinity/salinity as their causa mortis, occasionally subject to weak currents. The preferential preservation of flexed shrimps and isolated pleons corroborates this interpretation. Conchostracans, recorded in distinct levels, indicate episodes of mass mortality, variable transport and temporal mixing, and at least one faunal change. During the fossilization, primary P and Ca from shrimps and fishes probably generated phosphates, which finally altered to Fe oxy-/hydroxides, yielding a mixed elemental composition, not expressed in other mineralogies than Fe oxy-/hydroxides. The original calcite of ostracod valves likely has been dissolved/replaced by a K-rich aluminosilicate, or by a precursor phase. Plants were preserved by Fe oxy-/hydroxides or by kerogenisation. Previous studies show that marine ingression of Tethyan waters into the central segment of the proto-South Atlantic gulf flooded the continental scale axial river system captured by the Tucano rift basin, affecting base level up to the Araripe Basin. Here it is interpreted that tributary river systems with relatively steeper stream gradients were less affected by marine transgression than the axial system, resulting in local freshwater riverine influx across the elongated epeiric sea developed over the interior rift basins of NE-Brazil, resulting in a mixed biota of distinct water salinities that alternate in the Amargosa Bed type-section.
Keywords: Amargosa Bed; Aptian; Biostratinomy; Fossil preservation; Marizal Formation; Tucano Basin